Test equipment application for special endurance building in racing skiers and biathletes - Korchevoy, L. N.; Gonchar, E. A.; Karpushkina, O. I. (Theory and Practice of Physical Culture, 2017)
The study considers some issues of special endurance building in junior racing skiers and biathletes. Objective of the study was to improve the express-test methods to obtain the performance and technical skills rating data of racing skiers and biathletes. The study was designed to assess benefits of athlete`s fitness and performance test equipment and methods by a practical experiment.